A case of empyema necessitatis. - Tonna, I; Conlon, C; Davies, R (2007)
We present a case of empyema necessitatis presenting with an inflammatory cellulitis of the chest wall. Most of the cases previously reported were due to tuberculosis, pneumococcus or actinomycosis, with only a few cases being due to Staphylococcus aureus, as in this case. Early treatment with antibiotics and surgical drainage can prevent further complications.